Pengaruh Kepemilikan Manajemen dan Good Corporate Governance terhadap Penerapan Triple Bottom Line dengan Kinerja Keuangan sebagai Pemoderasi pada Perusahaan Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Anggraeni, Anggraeni; Indriyani MS, Eka; Raprayogha, Rusdi (Study of Scientific and Behavioral Management, 2024)
This study aims to examine the effect of managerial ownership and good corporate governance on the triple bottom line, with financial performance as a moderator. The plantation sub-sector industry in Indonesia has contributed 54.99% of total GDP. This study uses moderated regression analysis. The sampling technique used is purposive sampling with a sample size of 10 companies for 3 years with a reporting period of 2020-2022. The results of the study partially show that management ownership has a positive and significant effect, while good corporate governance with the independence of commissioners, the board of commissioners has a positive and significant effect, while the audit committee, the board of directors has a negative and significant effect on the implementation of the triple bottom line. Simultaneously, the variables of management ownership and good corporate governance have a significant effect on the implementation of the triple bottom line. The results of the MRA financial performance study do not moderate the variables of management ownership and the Good Corporate Governance variable. This study still has shortcomings such as the research period, the minimum number of samples so that it is less able to provide the actual condition of the company.